2019
DOI: 10.3390/ijerph16020174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Developmental Arsenic Exposure on the Social Behavior and Related Gene Expression in C3H Adult Male Mice

Abstract: Arsenic is carcinogenic and teratogenic. In addition, it is also a developmental neurotoxicant. Little is known however about the effect of arsenic exposure during brain development on social behavior. This study aimed to detect the effect of developmental arsenic exposure on social behavior and related gene expression in C3H adult male mice. Pregnant C3H mice were exposed to sodium arsenite (NaAsO2, 85 ppm in the drinking water) from gestational day (GD) 8 to 18. The F1 generation male pups from different mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
4
26
0
Order By: Relevance
“…Recently we have reported that developmental VPA and arsenic exposure impaired social behavior by modulating serotonin receptors and decreasing BDNF [28,43]. In the present study, we found downregulation of mRNA expression levels of social behavior related gene serotonin receptor 5HT5B and neurotrophic factors BDNF in the prefrontal cortex of male and female rats exposed to DE-SOA.…”
Section: Discussionsupporting
confidence: 68%
“…Recently we have reported that developmental VPA and arsenic exposure impaired social behavior by modulating serotonin receptors and decreasing BDNF [28,43]. In the present study, we found downregulation of mRNA expression levels of social behavior related gene serotonin receptor 5HT5B and neurotrophic factors BDNF in the prefrontal cortex of male and female rats exposed to DE-SOA.…”
Section: Discussionsupporting
confidence: 68%
“…Prenatal exposure to alcohol and arsenic has been shown to cause developmental neurotoxicity, affecting intellectual, emotional, and social functions permanently throughout later life [22,[24][25][26][27][28][29]. In the reporter transgenic mice, we observed RFP reporter expression, which reflects prior activation of HS signaling, in both neurons and glial cells broadly in the postnatal brain.…”
Section: Tracing the Lineage Of Cells Prenatally Affected By Environmmentioning
confidence: 77%
“…Arsenite is an inorganic form of arsenic, a metalloid naturally found in soil, air, and water in some zones of the world. Cumulative evidence from epidemiological and animal studies indicates that arsenic exposure in utero or in early childhood causes developmental neurotoxicity, affecting intellectual functions throughout life [24][25][26][27][28][29].…”
Section: Tracking Of the Cell Lineages Affected By Prenatal Exposure mentioning
confidence: 99%
“…In the present study, we found downregulation of mRNA expression levels of social behavior-related gene serotonin receptor 5HT5B and neurotrophic factor BDNF in the prefrontal cortex of male and female rats exposed to DE-SOA. Among serotonin receptors, 5HT5B was selected because this receptor is involved in social behavior [ 42 ]. BDNF is involved in synaptic plasticity which is critical for learning and memory functions.…”
Section: Discussionmentioning
confidence: 99%